2022
DOI: 10.3390/min12050634
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Operational Effectiveness of Innovative Circuit for Production of Crushed Regular Aggregates in Particle Size Fraction 8–16 mm

Abstract: The purpose of this paper is to analyze a modern and unique technological system producing common aggregates at the Imielin Dolomite Mine. The installation was built on the basis of inventions of AGH UST and consists of an impact crusher, innovative screens WSR and WSL, light fraction separator SEL and hard fraction separator SET, low-pressure hydrocyclone NHC and infrastructure. The study was carried out on the crusher and screen on the example of production of aggregates with grain size 8–16 mm from dolomite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The flakiness index for grain classes below 16 mm was below 10%, showing an improvement in this parameter compared to the feed ( Table 2 ). Gawenda et al [ 30 ] propose that the geometric parameters of aggregates are modified as a result of the secondary classification of the products after the crushing process. This classification could be conducted on slot screens so as to separate out flaky grains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flakiness index for grain classes below 16 mm was below 10%, showing an improvement in this parameter compared to the feed ( Table 2 ). Gawenda et al [ 30 ] propose that the geometric parameters of aggregates are modified as a result of the secondary classification of the products after the crushing process. This classification could be conducted on slot screens so as to separate out flaky grains.…”
Section: Resultsmentioning
confidence: 99%
“…This crucial aggregate property has been investigated from many aspects. For instance, Räisänen and Mertamo [ 23 ], Hofer et al [ 24 ], Gawenda [ 2 , 25 ], Rajan and Singh [ 26 , 27 ], Köken [ 28 ], Köken and Lawal [ 29 ], Strzałkowski et al [ 15 ] and Gawenda et al [ 30 , 31 ] indicated that the shape properties of rock aggregates are dependent upon the rock manufacturing processes. In other words, different rock crushers have different impacts on rock aggregate flakiness, which ultimately affects the mechanical parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental operation in material enrichment processes is the screening process. This process enhances the material's utility, allowing for the attainment of a uniform grain composition [1][2][3]. In most industrial sectors, screens are used for this purpose.…”
Section: Introductionmentioning
confidence: 99%